Impact of the counts density of calibration image and the image reconstruction parameters in 131I SPECT image quantification - Samira Marques Carvalho; Ana Paula Marques Costa; Celso Dario Ramos; Sérgio Querino Brunetto; Daniel Alexandre Baptista Bonifácio (Brazilian Journal of Radiation Sciences)
Iodine-131 (131I) has been used for diagnosis and therapy in Nuclear Medicine Centers in Brazil for more than 50 years. The present study aims to investigate the impact of the counts density and the reconstruction parameters in the calibration factor determination and  in the image quantification, considering the reality of Brazilian dosimetry studies. For this task, images were quantified using calibration images with high and low counts density and reconstructed adopting two different parameters approaches, usually employed in patients images.  SPECT quantification results presented in this work follow other previous 131I SPECT studies and suggest that, due to the long time interval between the first e last image, as required by the Brazilian guideline, the image quantification accuracy can be improved if the counts density in calibration measurements is considered.